Feodalizmo Vakarų Europoje genezė ir reikšmė pasaulio istorijos procesui: L. Vasiljevo ir E. Gudavičiaus sampratos - Babinskas, Nerijus (Lietuvos istorijos studijos, 2004)
The purpose of this article is to compare E. Gudavičius’ conception of feudalism with the Russian orientalist L. Vasilyev’s attitude to this issue. Both historians treat themselves as Marxists (in the Western meaning of it, i.e. supporters of the Asian mode of production). Consequently, their views on the development of the history of mankind are similar but not equal. In this article, feudalism is treated as a historical and socioeconomic formation and some stage of human development during which the feudal mode of production was dominating. L. Vasilyev describes the stage of feudalism in Western Europe as the age of orientalisation of social structure, i.e. as a regress. Only the rebirth of Antiquity bore capitalism. E. Gudavičius stresses that feudalism created an individual producer (peasant) farm and consequently it was an essential progress in the social development of the societies of Western Europe. The character of the social structure of Germanic kingdoms in the early Middle Ages differed essentially from oriental societies in the stage of early politogenesis. The reason for that was the alodization of Germanic society. So the prefeudal stage (the term of E. Gudavičius) as well as the feudal stage was unique in both chronological and geographical senses (as for this aspect, Western Europe is comparable maybe only with medieval Japan). In the early Middle Ages, a necessary condition of the feudalisation of the periphery of Western Europe was the influence of the neighbouring (already feudal) countries. Otherwise, the social structure of peripheral societies would have been developing like in the Orient. L. Vasilyev affirms convincingly that market relations in Germanic society in the early Middle Ages were suppressed by vertical (subordinating) and corporative connections. In this sense, Western Europe became similar to the Orient. Nevertheless, the main difference was that private property remained in Western Europe. Private property enabled the development of market relations when civilization and technologies were restored. Medieval cities and burghers undermined feudalism and were the first sprouts of the capitalist structure. L. Vasilyev’s statement that capitalism is the consequence of a structural rebirth of Antiquity is not very convincing. The structural heritage of Antiquity was a primary stimulus during the process of the genesis of feudalism. Later, feudalism developed spontaneously and the part of the heritage of Antiquity was only auxiliary. It is very doubtful that the historical experiment of the structural synthesis took place in medieval Western Europe (according to L. Vasilyev’s conception it also took place in the Hellenistic Orient and in the Byzantine Empire). Already, during the stage of the genesis of feudalism, a social mutation (i.e. qualitative change) took place in Western Europe. So, in general, there was no more structural synthesis but spontaneous development. On the other hand, the mentioned L. Vasilyev’s conception was not adapted to much more prospective cases like the Philippines and especially Latin America.